Analysis of Factors Affecting Firm Innovation: An Empirical Investigation for Ethiopian Firms - ÇOKGEZEN, MURAT (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
The present study concentrates on answering following questions: (i) Do firm's internal factors such as size, age, ownership, R&D spending, and exporting significantly predict the propensity of firms to engage in innovative activities in Ethiopia? (ii) Do firm's external factors, namely, access to finance and competition, significantly predict the propensity of firms to engage in innovative activities in Ethiopia? The data source of the paper is a survey conducted by World Bank in 2015 on Ethiopian firms. Then, the factors influencing the innovativeness of Ethiopian firms are analyzed by using a logistic regression model. Results obtained through logistic regression suggest that internal factors such as the size of the firms, education level of the employees, technology adoption capability of managers, on-job training, and R&D expenditures have a significant positive impact on both types of innovations, while private and foreign ownership were only found to be significant for process innovation. Estimations also showed that access to finance has a significant (positive) impact on product innovation and the impact of the competition level is significant (negative) only in terms of process innovation. Most importantly, we found that, disregarding their statistical significance, all explanatory variables influence both process and product innovation in the same direction, probably because of the positive correlation between the two.
Keywords: Innovation; Ethiopia; Logistic regression; OWNERSHIP STRUCTURE; PERFORMANCE; COUNTRIES; DETERMINANTS; COMPETITION; GOVERNANCE; IMPACT; SIZE